2019
DOI: 10.1371/journal.pone.0221875
|View full text |Cite
|
Sign up to set email alerts
|

Falls among community-dwelling older adults in Ethiopia; A preliminary cross-sectional study

Abstract: BackgroundFalls among older adults is a common precipitating factor for unintentional injuries and represent a major health problem associated with increased morbidity, mortality, and health care cost in low-and-middle-income countries. The burden of fall in this population is well established in high-income countries and scant attention is given to this precipitating factor in low-and-middle-income countries, including Ethiopia. Therefore, this study aimed to estimate the prevalence and factors associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 34 publications
0
12
0
8
Order By: Relevance
“…According to prior studies, uneducated elders are twice as likely to experience falls as educated people. 22 , 37 , 38 Poor educational status and/or uneducated older adults may lack a proper understanding of the consequences of old age and, health related age and life adjustments. 38 Therefore, dramatic changes in education and knowledge would improve the health of the older adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to prior studies, uneducated elders are twice as likely to experience falls as educated people. 22 , 37 , 38 Poor educational status and/or uneducated older adults may lack a proper understanding of the consequences of old age and, health related age and life adjustments. 38 Therefore, dramatic changes in education and knowledge would improve the health of the older adults.…”
Section: Discussionmentioning
confidence: 99%
“…22 , 37 , 38 Poor educational status and/or uneducated older adults may lack a proper understanding of the consequences of old age and, health related age and life adjustments. 38 Therefore, dramatic changes in education and knowledge would improve the health of the older adults. 39 In addition, our findings reveal a link between income and falls.…”
Section: Discussionmentioning
confidence: 99%
“…Studies had reported a wide range of risk factors for fall; age, gender, severity of visual impairment, body mass index, psychosocial, physical environment, fear of fall, depression, decreased vestibular reflexes, decreased muscle strength, increasing postural sway, concurrent medical issues, poly-medications, and pre-existing medical co-morbidities [2,10,11]. Polypharmacy is also one of the important risk factor for falling and the association is stronger if the medications include fall riskincreasing medications [12].…”
Section: Introductionmentioning
confidence: 99%
“…Due to declining physical health, seniors are often worried about their personal safety. The slippery surface of the road can easily lead to younger adults falling, let alone frail seniors [ 96 ]. Seniors may hesitate to go out if they know there are many slippery surfaces in the area or may be encouraged to go outside if slip-resistant measures, such as anti-slip mats and non-slip tiles, are in place.…”
Section: Discussionmentioning
confidence: 99%